Physiological and cognitive measures during prolonged sitting: Comparisons between a standard and multi-axial office chair. (July 2019) - Triglav, Joseph; Howe, Erika; Cheema, Jaskirat; Dube, Blaire; Fenske, Mark J.; Strzalkowski, Nicholas; Bent, Leah
Abstract: Prolonged sitting, common in many workplaces, reduces blood flow to the lower limb and has negative health outcomes. CoreChair is an active-sitting chair that encourages increased movement to help mitigate these outcomes. Physiological and cognitive measures were recorded in ten subjects over 4 h of sitting in both the CoreChair and a traditional office chair. Sitting in both chairs led to increases in calf circumference ( p < 0.0001), reduced tactile sensitivity ( p = 0.02), and a cognitive decline in attention ( p = 0.035) over time. However, the increase in calf circumference was smaller in the CoreChair at the second (p = 0.017) and third hour (p = 0.012) compared to the traditional chair. Additionally, for the attention task, the traditional chair generated more attention-task errors (p = 0.005), while no changes were observed with the CoreChair (p = 0.13). These findings suggest that during prolonged sitting CoreChair may have modest physiological and cognitive benefits compared to a traditional chair. Highlights: All measured physiological changes were affected by long duration sitting. Increase in calf circumference, and therefore venous pooling was reduced with active sitting. While foot sole skin sensitivity decreased across long duration sitting, it was not improved with the active chair. Decreased attention over time of sitting was observed, which was partially mitigated by sitting in the active chair.